2009
DOI: 10.1093/carcin/bgp211
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone enhances head and neck cancer therapies via inhibition of signal transducer and activator of transcription-3

Abstract: Treatment of human head and neck squamous cell carcinoma (HNSCC) cell lines with guggulsterone, a widely available, well-tolerated nutraceutical, demonstrated dose-dependent decreases in cell viability with EC(50)s ranging from 5 to 8 microM. Guggulsterone induced apoptosis and cell cycle arrest, inhibited invasion and enhanced the efficacy of erlotinib, cetuximab and cisplatin in HNSCC cell lines. Guggulsterone induced decreased expression of both phosphotyrosine and total signal transducer and activator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 40 publications
1
76
0
1
Order By: Relevance
“…In a xenograft model of HNSCC, GS treatment resulted in increased apoptosis and decreased expression of STAT3. Therefore, these results suggest that the inhibition of STAT3 and HIF-1α by GS provide a strong rationale for further clinical investigation of this compound in the treatment of HNSCC [263][264][265]. Moreover, the reported safety of GS [266] makes it a good candidate for complementary and preventive therapy.…”
Section: Guggulsteronementioning
confidence: 97%
“…In a xenograft model of HNSCC, GS treatment resulted in increased apoptosis and decreased expression of STAT3. Therefore, these results suggest that the inhibition of STAT3 and HIF-1α by GS provide a strong rationale for further clinical investigation of this compound in the treatment of HNSCC [263][264][265]. Moreover, the reported safety of GS [266] makes it a good candidate for complementary and preventive therapy.…”
Section: Guggulsteronementioning
confidence: 97%
“…Based on these pharmacokinetic observations, it is possible that the concentrations of GL needed to inhibit cancer cell growth may be achievable in humans. More recently (Leeman-Neill et al, 2009), we reported that treatment with GL (3 mol standardized to zGug, daily for 3 weeks) resulted in the enhancement of cetuximab activity in xenograft model of head and neck cancer.…”
Section: Discussionmentioning
confidence: 97%
“…4). Based on these data, the remaining HCS operation runs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were conducted in Cal33 cells with passage #s <20 and with IL-6 that had been reconstituted and stored at -80°C for £4 weeks.…”
Section: ‰ Hcs For Inhibitors Of Il-6-induced Pstat3mentioning
confidence: 99%
“…1,2,4,[6][7][8] Head and neck squamous cell carcinoma (HNSCC) tumors and cell lines exhibit high pSTAT3-Y705 expression levels. 4,5,[7][8][9][10][11] HNSCC is the eighth leading cause of cancer worldwide with an incidence of *600,000 new cases and *300,000 deaths per annum. [12][13][14] Smoking, alcohol use, genetics, and human papillomavirus (HPV) infection contribute to the carcinogenesis and pathology of HNSCC.…”
Section: Introductionmentioning
confidence: 99%